ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE DAN TINGKAT PROFITABILITAS TERHADAP PENGUNGKAPAN INFORMASI AKUNTANSI (Studi Empiris pada Top 50 Emiten dengan Skor CG Tertinggi Hasil IICD melalui Pendekatan ASEAN Corporate Governance Scorecard Periode 2012-20 - Alhamra, Insan Thariq; Hermiyetti, Hermiyetti (Prosiding Seminar Nasional INDOCOMPAC)
The object of this study is to analyze the influence of Good Corporate Governance and profitability to disclosure of accounting information. The results of this study can be used as a reference for investors to determine how far the influence of Good Corporate Governance and the level of profitability on the disclosure of accounting information on non-financial companies listed on the Stock Exchange in the period 2012-2013. This research used purposive sampling during 2012 to 2013 in order to obtain 20 samples. This research uses the analysis method descriptive, classic assumption test, test hypotheses using SPSS 20.Hypothesis testing results show that the level of profitability is partially positive effect on the disclosure of accounting information, because it shows the success of the company's profitability thus affecting the level of disclosure of corporate accounting. Good Corporate Governance is partially no effect on the disclosure of accounting information, GCG has no effect on the disclosure of accounting information, because it is still a lack of attention companies IICG as an institution conducting the survey that showed weak CGPI Good Corporate Governance for companies tersebut.Secara simultaneous influence Good Corporate Governance and the level of profitability can be a positive influence on the disclosure of accounting information. Companies that have high levels of profitability and good corporate governance will tend to disclose more accounting information. Key words: Good Corporate Governance, Level of Profitability, Disclosure of Accounting Information